Pengembangan Bahan Ajar Berbasis Android pada Materi Tata Nama Senyawa Hidrokarbon - suci dessia; rini muharini (PendIPA Journal of Science Education, 2022)
The aim of this study was to determine the feasibility of android-based teaching materials in the nomenclature of hydrocarbon compounds. The development of android teaching materials can make it easier for students to access teaching materials in a practical way and help understand the nomenclature of hydrocarbon compounds, and it is hoped that students can take advantage of information technology in terms of learning. The research used research and development methods with the ADDIE model. Data collection technique was using validation questionnaires and response questionnaires. The data were analyzed descriptively qualitatively. The results of the analysis show that the validation of the material aspect is 91.39% with very feasible criteria , media aspect validation 90% in the very feasible criteria, 94.73% linguist validation in the very feasible criteria, the chemistry teacher response questionnaire was 93.75% with very good criteria, the student response questionnaire for the small group trial obtained a score of 89.32% with very good criteria and the results of the student response questionnaire for the broad scale trial were 89.45% with very good criteria. It can be concluded that android-based teaching materials are in the form of applications with a capacity of 42 MB which were developed with very good student responses and very good teacher responses, so that these teaching materials are very suitable to be used as learning tools.